Analysis of Psychosocial Factors Affecting Physical Activity Behaviour of People with Type 2 Diabetes Mellitus in Indonesia - Rondhianto; Kushariyadi; Pinky Issabella Nanda Basuki (Nursing and Health Sciences Journal (NHSJ), 2023)
Physical activity exercise is an essential component in comprehensive diabetes management. Non-adherence to physical activity exercises can lead to poor metabolic control, causing increased complications, morbidity, and premature death due to diabetes. One of the factors that can determine the behavior of physical activity is the psychosocial factor of people with T2DM. The study aims to assess the effect of psychosocial factors on physical activity behavior. This study was an analytical observational with a cross-sectional approach. The sample size was 138 respondents with multistage random sampling. The dependent variable was physical activity behavior, and the independent variables were psychosocial factors (knowledge, coping, distress, perceptions of family support, and perceptions of nurse support). Data analysis used multiple linear regression (α=0.05). Psychosocial factors that influenced the physical activity behavior were distress (p=0.001 < α=0.05). Meanwhile, knowledge, coping, perceived family support, and perceived nurse support did not affect physical activity behavior (p=0.684; p=0.919; p=0.235; p=0.108 > α=0.05) with Adjusted R2=0.113 (F=4.502; p=0.001 < α=0.05). Psychosocial factors that influence physical activity behavior in T2DM patients are diabetic distress. Therefore, health workers, in providing health services as much as possible, must be able to prevent and reduce diabetes distress to increase the physical activity behavior of people with T2DM.